An evaluation of the collections of selected university of the Philippines Diliman Libraries on christian and Islamic sacred scriptures - Roque, Nicolae Ignatius I.; Faderon, Rosalie B. (Quezon City Institute of Library Science, University of the Philippines Diliman, 2002)
The two major religions in the Philippines are Christianity and Islam. The sacred scriptures of the two are the Bible and the Koran, respectively. This study evaluated the adequacy of the collections of these two sacred books and related materials in selected libraries in the University of the Philippines (UP) Diliman in terms of quantity, quality, availability and accessibility in relation to user demand. The libraries studied were three sub-units within the Main Library - the Social Science Section, General Reference Section and the Filipiniana Section - and the Institute of Islamic Studies (IIS) Library. User demand was defined by the collections' clientele, whether active - those who have already used the materials under study - or potential - those who have not yet used the materials but have expressed a desire to do so. This is determined through two means: survey and documentary analysis, which shows book use.
The survey used the purposive sampling scheme, choosing those who were predisposed to use the materials in the collections. The population from which a sample was taken was the members of the religious organizations in UP Diliman - Christian student organizations and the UP Muslim Students' Association (UP MSA). The documentary analysis focused on the books' frequency of use, or how often they were borrowed. Except for the survey results, data were evaluated by library. One hundred respondents were surveyed for the Bible clientele, all of whom were affiliated with Christian organizations in UP Diliman, while 14 were surveyed for the Koran clientele, all of whom were from the UP Muslim Student's Association (UP MSA). Of the 100 respondents from Christian student organizations in UP, the survey extracted 41 active clients and 54 potential clients. Of the 14 respondents from the UP Muslim Student Association, eight were found to be active clients and five to be potential clients. In relation to very low user demand for its materials, the Bible collection of the Filipiniana Section is highly adequate in quantity, variety and availability. But the collection itself has poor accessibility. The section's Koran collection, on the other hand, is highly inadequate with only two materials - two copies of the same book. There is high user demand for the materials in the Bible collection of the Social Science Section, and the collection itself proves adequate in all aspects-quantity, quality, availability and accessibility. The same may be said of the section's Koran collection. There is very high user demand for the materials in the Bible collection of the General Reference Section. The collection of Bibles is highly inadequate while the collection of related materials proves adequate in all aspects. The library's Koran collection is highly inadequate in quantity and variety with only two materials. There is high demand for materials in the Koran collection of the Institute of Islamic Studies (IIS) Library as it is the obvious source of such materials. The library's collection of Koran is adequate, but its collection of related materials could yet improve in quantity and variety. The Koran collection of the Filipiniana Section should be vastly improved in quantity and variety as a potential client of a Koran collection, or a Moslem, would be a potential client for the Filipiniana Section. The General Reference Section should have complete copies of the Bible, perhaps the New International Version, and it seems to be the most popular version among clients. The library should also have much more Koran-related materials.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: University of the Philippines (Diliman) Library; Religious literature; College libraries -- Philippines -- Quezon City